EDUCATION ON TOP GRAFTING TECHNIQUES AS AN INNOVATIVE SOLUTION TO INCREASE WATERMELON PRODUCTION AT THE FARMER LEVEL - Assauwab, Muhammad Husaini; Deden Sumoharjo; Anuar Ramut; Husainah Yusuf; Kartono; Joharsah; Hadirin; Habibul Akram; Muridha Hasan (Jurnal Pengabdian Indonesia (JPI), 2025)
Watermelon production among local farmers often faces challenges such as pest and disease attacks that cause a decline in crop yields. Grafting is an innovative method that can increase plant resistance and productivity. This community service activity aims to educate farmers about grafting techniques for watermelons. The methods used include training sessions, hands-on demonstrations, and on-site practical guidance. The results of the activity show an increase in farmers' understanding of grafting techniques and their application in watermelon cultivation. It is hoped that this education will contribute to increased watermelon production and farmer well-being.